A flexible and transparent β-Ga2O3 solar-blind ultraviolet photodetector on mica. (1st October 2020) - Sui, Yanxin; Liang, Huili; Huo, Wenxing; Wang, Yan; Mei, Zengxia
Abstract: In the present work, we report a flexible transparent β- Ga2 O3 solar-blind ultraviolet (UV) photodetector (PD) fabricated on a mica substrate. A laminated a-Ga2 O3 /Ga/a-Ga2 O3 structure is thermally annealed at 1050 °C, forming a β- Ga2 O3 film incorporating Ga nanospheres. A PD based on this nanocomposite film has a spectrum response peak at 250 nm, an extremely low dark current of 0.6 pA at a 10 V bias, a very high Ilight /Idark ratio of 3 × 10 6, and a fast recovery speed of less than 50 ms. Robust flexibility is demonstrated by bending tests and 10 000 cycles of a fatigue test with a radius as small as 8 mm. Compared to a room-temperature-fabricated flexible amorphous Ga2 O3 (a-Ga2 O3 ) PD, the flexible β- Ga2 O3 PD on mica exhibits improved solar-blind UV photoresponse characteristics. The insertion of a gallium interlayer and treatment by high-temperature post annealing are proposed to contribute to a better stoichiometry and lattice order of the β- Ga2 O3 thin film, as evidenced by the pronounced Raman peaks related to the GaI (OI )2 and GaI O4 vibration modes in β -phase Ga2 O3 . Our research is believed to provide a simple and practical route to achieving flexible transparent β- Ga2 O3 solar-blind UV PDs, as well as other devices such as flexible transparent phototransistors and power rectifiers.